1998
DOI: 10.1128/aem.64.3.948-954.1998
|View full text |Cite
|
Sign up to set email alerts
|

PCR Amplification of Ribosomal DNA for Species Identification in the Plant Pathogen Genus Phytophthora

Abstract: We have developed a PCR procedure to amplify DNA for quick identification of the economically important species from each of the six taxonomic groups in the plant pathogen genusPhytophthora. This procedure involves amplification of the 5.8S ribosomal DNA gene and internal transcribed spacers (ITS) with the ITS primers ITS 5 and ITS 4. Restriction digests of the amplified DNA products were conducted with the restriction enzymesRsaI, MspI, and HaeIII. Restriction fragment patterns were similar after digestions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0
15

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(77 citation statements)
references
References 34 publications
2
57
0
15
Order By: Relevance
“…A portion of the P. infestans 5Á8S subunit and ITS2 region of rDNA was chosen as the target for the first set of LAMP primers (ITSII primers). This region was chosen because of the sensitivity and specificity achieved with other previously developed PCR and qPCR assays (Tooley et al 1997;Trout et al 1997;Ristaino et al 1998;Lees et al 2012). The LAMP ITSII primers had sensitivity comparable to several other published LAMP assays (limit of detection of 2 pg P. infestans DNA).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A portion of the P. infestans 5Á8S subunit and ITS2 region of rDNA was chosen as the target for the first set of LAMP primers (ITSII primers). This region was chosen because of the sensitivity and specificity achieved with other previously developed PCR and qPCR assays (Tooley et al 1997;Trout et al 1997;Ristaino et al 1998;Lees et al 2012). The LAMP ITSII primers had sensitivity comparable to several other published LAMP assays (limit of detection of 2 pg P. infestans DNA).…”
Section: Discussionmentioning
confidence: 99%
“…Potential applications of such diagnostic repetitive sequence of P. infestans DNA. The internal transcribed spacer (ITS) regions of ribosomal DNA are commonly used in diagnostics due to their relatively high copy number and species specificity (Cassidy et al 1984;Russell et al 1984;Tooley et al 1997;Trout et al 1997;Liew et al 1998;Ristaino et al 1998;Lees et al 2012;Hussain et al 2013). Following the work of Niepold and Sch€ ober-Butin, an ITS-targeting PCR assay was developed and tested for specificity.…”
Section: Introductionmentioning
confidence: 99%
“…Further determination of other species as causal pathogens is possible by comparing SSCP profiles with the Phytophthora species examined in this study and reported previously (Kong et al 2003). These features make SSCP analysis a superior technique to other existing molecular fingerprinting methods such as restriction fragment length polymorphism (RFLP) (Förster et al 1989;Ristaino et al 1998) and isozyme analysis (Nygaard et al 1989;Oudemans and Coffey 1991); both methods usually require examining several molecular profiles to key an isolate to species.…”
Section: Resultsmentioning
confidence: 80%
“…SSCP patterns in silver-stained gels can be differentiated visually without specialized equipment normally required by other DNA fingerprinting methods for differentiation of Phytophthora spp. (Förster et al 1989;Tooley et al 1997;Ristaino et al 1998 Fig. 4 Single-strand conformation polymorphism profiles of ITS-1 for Phytophthora ramorum (Ram) and its ecologically close associates.…”
Section: Resultsmentioning
confidence: 99%
“…The ARDRA procedure has been widely used for the identification of fungal phytopathogens, e.g. [25,26,31] and clinical fungi, e.g. [27,28].…”
Section: Restriction Map Analysismentioning
confidence: 99%